A study on foreign ownership and the property prices in Singapore. - Lim, Darrell Wei Way. (2011)
This paper seeks to examine whether foreign ownership of residential property in Singapore has an impact on property prices. In the past couple of years, property prices in Singapore have been escalating to new highs. Many analysts and experts have attributed this rise to an increase in demand especially from foreigners and permanent residents. This research paper attempts to analyze the relationship between foreign ownership and property prices in Singapore. Other economic factors such as GDP growth, CPI growth, and SIBOR are also added in this study as control variables. This study was able to statistically show that there is a negative relationship between foreign ownership and the price-to-rent ratio in the non-landed and terrace houses property classes.